2013
DOI: 10.1016/j.taap.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the chemical reactivity and nephrotoxicity of N-acetyl-S-(1,2-dichlorovinyl)-l-cysteine sulfoxide, a potential reactive metabolite of trichloroethylene

Abstract: N-Acetyl-S-(1,2-dichlorovinyl)-L-cysteine (NA-DCVC) has been detected in the urine of humans exposed to trichloroethylene and its related sulfoxide, N-acetyl-S-(1,2-dichlorovinyl)-L-cysteine sulfoxide (NA-DCVCS), has been detected as hemoglobin adducts in blood of rats dosed with S-(1,2-dichlorovinyl)-L-cysteine (DCVC) or S-(1,2-dichlorovinyl)-L-cysteine sulfoxide (DCVCS). Because the in vivo nephrotoxicity of NA-DCVCS was unknown, in this study, male Sprague-Dawley rats were dosed (i.p.) with 230 µmol/kg b.w.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…We did observe an increase in KIM-1 staining in PCE-treated mice, showing that kidney is a target tissue in the mouse. It has been postulated that the bio-activation of TCVC and NAcTCVC, catalyzed by renal b lyase or other enzymes such as flavin monooxygenase and CYP3A, is a critical step for nephrotoxicity of PCE (Irving et al, 2013;Lash et al, 1994). It is likely that CYP2E1 may also play a role in sulfoxidation of cysteine and n-acetyl cysteine conjugates of PCE, as it was shown that CYP2E1 is involved in sulfoxidation of S-methyl N, N-diethylthiolcarbamate (Madan et al, 1995) and diethyldithiocarbamate methyl ester (Madan et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We did observe an increase in KIM-1 staining in PCE-treated mice, showing that kidney is a target tissue in the mouse. It has been postulated that the bio-activation of TCVC and NAcTCVC, catalyzed by renal b lyase or other enzymes such as flavin monooxygenase and CYP3A, is a critical step for nephrotoxicity of PCE (Irving et al, 2013;Lash et al, 1994). It is likely that CYP2E1 may also play a role in sulfoxidation of cysteine and n-acetyl cysteine conjugates of PCE, as it was shown that CYP2E1 is involved in sulfoxidation of S-methyl N, N-diethylthiolcarbamate (Madan et al, 1995) and diethyldithiocarbamate methyl ester (Madan et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with reports that in the absence of hepatic metabolism of GSH conjugates, PERC is more cytotoxic than TCE to isolated kidney cells (Lash et al, 2007), and that DCVC is less nephrotoxic than TCVC in vivo (Birner et al, 1997). However, kidney cancer hazard evidence in humans is more potent for TCE than PERC (Guha et al, 2012), indicating that bioactivation to downstream reactive sulfoxides, DCVCSO and NAcDCVCSO, may be most critical part of cancer etiology in the kidneys (Irving et al, 2013; Lash et al, 1994). It is also plausible that lower levels of DCVC and NAcDCVC, as compared to those of TCVC and NAcTCVC, are the product of a higher conversion rate to their corresponding sulfoxides, a process mediated by hepatic cytochrome P450 3A enzymes (Werner et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, TCVC can be detoxified via N-acetylation to form N-acetyl-S-(1,2,2-trichlorovinyl)cysteine (NAcTCVC). Both TCVC and NAcTCVC can further undergo metabolic activation to generate reactive sulfoxides, which may contribute to the kidney effects of PERC (Irving et al. 2013).…”
Section: Introductionmentioning
confidence: 99%